IMPROVING THE DESIGN OF LOW VOLUME SEALED ROADS IN TANZANIA - Mfinanga, David A.; Mwakyami, Lusekelo A. (Tanzania Journal of Engineering and Technology, 2018)
The main objective of the study was to identify appropriate road designs for Low Volume Sealed Roads (LVSRs) with the aim of improving the design of such roads in Tanzania. The study was conducted in Dar es Salaam and Morogoro regions in Tanzania where data for LVSRs were collected from primary and secondary sources in the two regions. The study found that by using an improved pavement design method specifically meant for LVSRs results in cost savings for LVSRs of up to 51% compared with the conventional method of pavement design in Tanzania. The study recommends that the pavement design method for lightly trafficked sealed roads in southern Africa developed by Transport Research Laboratory, which was found to be most cost-effective, be used to design (or develop a procedure for design of) LVSRs in Tanzania and that the roads be preferably sealed with Otta seal or Surface dressing. The study also recommends that LVSRs in Tanzania be defined by a maximum traffic volume of 400 vpd.